The effects of whey protein on cardiometabolic risk factors. Issue 4 (20th November 2012) - Pal, Sebely; Radavelli‐Bagatini, Simone
Summary: Obesity has reached epidemic proportions worldwide. The health consequences of obesity are more dangerous when associated with the metabolic syndrome and its components. Studies show that whey protein and its bioactive components can promote greater benefits compared to other protein sources such as egg and casein. The aim of this paper is to review the effects of whey protein on cardiometabolic risk factors. Using PubMed as the database, a review was conducted to identify current scientific literature on whey protein and the components of the metabolic syndrome published between 1970 and 2012. Consumption of whey protein seems to play an anti‐obesity and muscle‐protective role during dieting by increasing thermogenesis and maintaining lean mass. In addition, whey protein has been shown to improve glucose levels and insulin response, promote a reduction in blood pressure and arterial stiffness, and improve lipid profile. The collective view of current scientific literature indicates that the consumption of whey protein may have beneficial effects on some symptoms of the metabolic syndrome as well as a reduction in cardiovascular risk factors.